HLA analysis of Sri Lankan Sinhalese predicts North Indian origin. - Malavige, G; Rostron, T; Seneviratne, S; Fernando, S; Sivayogan, S; Wijewickrama, A; Ogg, G (2007)
The origin of the Sinhalese population of Sri Lanka is debated. We subtyped HLA-A*02 in 101 Sinhalese and observed a preponderance of the rare allele HLA-A*0211 which was similar to reported frequencies in northern India. Taken with low-resolution typing for the remaining A, B, C, DR and DQ alleles, these data suggest a North Indian origin for the Sri Lankan Sinhalese.